2012
DOI: 10.9775/kvfd.2012.6348
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA Expression Pattern of Skeletal Muscle Regulatory Factors in Divergent Phenotype Swine Breeds

Abstract: SummaryMuscle regulatory factors (MRFs) play a major role in muscle growth and development. Thus, they are considered as candidate genes for meat production traits in pigs. These basic helix-loop-helix (bHLH) and paired box transcription factors together with Bone morphogenetic proteins, regulate myogenesis: they initiate the formation of muscle fibers and regulate the transcription of muscle specific genes. The objective of this study was to investigate the mRNA abundance of transcription factor (TF) genes (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
3
3
Order By: Relevance
“…Principal component analysis applied to gene expression data sets showed similar expression levels of MyoD and myogenin genes in different muscles in different pig breeds such as Duroc and Pietrain. These results differed from those in the current study, possibly because of species differences (avian/mammalian; Cinar and Fan, 2012). Taken together, these findings suggested possible coordinated regulation of MRF gene expression during skeletal muscle development in the embryonic stage.…”
Section: Discussioncontrasting
confidence: 57%
“…Principal component analysis applied to gene expression data sets showed similar expression levels of MyoD and myogenin genes in different muscles in different pig breeds such as Duroc and Pietrain. These results differed from those in the current study, possibly because of species differences (avian/mammalian; Cinar and Fan, 2012). Taken together, these findings suggested possible coordinated regulation of MRF gene expression during skeletal muscle development in the embryonic stage.…”
Section: Discussioncontrasting
confidence: 57%
“…Thus, different expression patterns could be due to the close proximity of the Myf6 and Myf5 genes on Sus scrofa chromosome 5. However, these findings were different from our results, which may be explained by the different species (avian/mammalian) (Cinar & Fan 2012). The expression levels of Myf5 were less than that of Myf6 in both BM and LM and showed different expression pattern in different muscle, and there was also a different pattern with Myf6 gene.…”
Section: Discussioncontrasting
confidence: 99%
“…PCA results have shown that MyoD gene expression in different muscle tissues was similar in Duroc and Pietrain pig breeds. However, these findings were different from our results, which may be explained by the different species (avian/mammalian) (Cinar & Fan 2012). Taken together, these findings suggested possible coordinated regulation of MyoD and Myf6 gene expression during skeletal muscle development.…”
Section: Discussioncontrasting
confidence: 99%
“…Taken together, we propose that there might exist certain differences in myogenesis among the three muscles. Furthermore, the myogenesis marker genes ( Myf4 , MyoD , BMP4 , Myf5 , and SRF ) [31,32,33,34], were significantly more highly expressed in PL, which confirmed that PL had higher myogenesis capacity (Figure 2g). The activation of myogenic progenitors (e.g., satellite cells) contributed to the myogenensis of adult skeletal muscle tissues [35], thus we propose that the PL may contain more active myogenic progenitors relative to PL and LDM.…”
Section: Resultsmentioning
confidence: 72%